NOBLE GASES IN THE EARTH'S MANTLE - Farley K.A.; Neroda E. (My University, 1998)
Noble gas isotopic ratios in mantle-derived samples require variability in the time-integrated ratio of volatile to lithophile elements in the Earth. Documentation of mantle 3He/4He variability is becoming increasingly complete, but for the heavier noble gases the picture is still partly clouded by the effects of atmospheric contamination of mantle samples. Nevertheless, clear variations in mantle Ne, Ar and Xe isotopic ratios exist, are apparently correlated with 3He/4He, and may be the product of varying degrees of mantle degassing. However, uncertainties in noble gas geochemical behavior and several conflicting observations leave open other possibilities. Recent Ne isotopic data are particularly important because they require that the atmosphere has not been closed to exchange with space. Derivation of much of the atmosphere from a source other than degassing of the mantle is a strong possibility that complicates efforts to model the geochemical evolution of the Earth.